URINARY INCONTINENCE IS MORE COMMON IN ADOLESCENT FEMALE ATHLETES WITH LOW ENERGY AVAILABILITY. Issue 3 (31st March 2019) - Whitney, Kristin E.; Holtzman, Bryan; Parziale, Allyson; Ackerman, Kathryn E.
BACKGROUND: Female Athlete Triad (Triad), an interrelated syndrome of low energy availability (EA), menstrual irregularity, and low bone mineral density. A broader, more comprehensive term was recently introduced by the International Olympic Committee: 'Relative Energy Deficiency in Sport' (RED-S). RED-S includes Triad, but also highlights the multiplicity of complex health and performance consequences of low EA and emphasizes that male athletes are also affected. The syndrome RED-S refers to impaired physiological function caused by relative energy deficiency including menstrual function, metabolism, bone health, immunity, protein synthesis, and cardiovascular health. Low EA has independent negative effects on reproductive function and gonadal steroid production. Urinary incontinence (UI) has many risk factors, including estrogen deficiency (which can be caused by low EA), depression, and participation in high-impact activities. A high prevalence of UI has been reported in female athletes participating in a variety of different sports. To date, research evaluating low energy availability as an independent risk factor for UI has been limited, particularly in a young female athlete population. The purpose of this study was to evaluate the association of UI and low EA in adolescent female athletes. METHODS: 1000 female athletes (ages 15–30 years) presenting to a sports medicine clinic completed a 476 question survey covering topics related to relative energy deficiency in sport (RED-S), including female athlete triad risk factors and athletic activity. For the purpose of this study, data was extracted from responses by subjects between 15–19 years of age. Low EA was defined as meeting = 1 criterion: self-reported history of eating disorder/disordered eating (ED/DE), high score on the Brief Eating Disorder in Athletes Questionnaire (BEDA-Q), and/or high score on the Eating Disorder Screen for Primary Care (ESP). UI was assessed through a modified form of the International Consultation on Incontinence Modular Questionnaire-Urinary Incontinence (ICIQ-UI Short Form). Descriptive statistics are expressed as mean ± standard deviation and associations between EA status and UI queries were assessed by chi-squared analysis (cut off for statistical significance was defined as: p<0.05). RESULTS: Of those who completed the survey, 70.8% were adolescents between 15 and 19 years of age. UI during athletic activities was reported by 14.4% of these athletes. Of those reporting UI, UI was significantly more common in those with low EA than those with adequate EA (54.9% vs. 45.1%, p=0.003). Age was not associated with UI in this subset (p=0.83). The median onset of UI was 1–2 years prior to completing the survey and the median frequency of UI over the previous year was reported as weekly. There was no significant correlation between the presence of menstrual dysfunction and UI (p=0.104). CONCLUSIONS: Our findings demonstrate that UI is a common problem among adolescent female athletes, occurring in 14.4% of 15-19 year old female athletes surveyed in this study. UI is more prevalent in adolescent female athletes with low EA in comparison to female athletes with adequate EA. These findings are consistent with those previously observed in studies involving older populations of adult female athletes with eating disorders, where UI was more prevalent in those with low EA in comparison to controls with adequate EA. These findings suggest a potential place for genitourinary disorders in the constellation of impaired physiologic functions considered associated with low EA in athletes/RED-S, and offers a window into a commonly overlooked clinical problem impacting young female athletes.